Editorial Preface - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak` (Idealogy Journal; Vol 6 No 1 (2021): Idealogy Journal (April 2021)DO - 10.24191/idealogy.v6i1.262, 2021)
Overview of the Idealogy of Arts and Social Science by the Chief and Deputy Chief Editor. Keywords: Arts; Social Science